2015
DOI: 10.1097/scs.0000000000002063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long-Term Prognosis and Prognostic Predictors in Severe Brain Injury Patients Undergoing Decompressive Craniectomy and Standard Care

Abstract: Decompressive craniectomy (DC) is widely used to treat acute subdural haematoma and hemispheric swelling following traumatic brain injury (TBI). The therapeutic effect of DC on severe TBI treatment is still controversial. The aim of our study was to evaluate effectiveness of DC treatment and seek some prognostic predictors. According to the therapy method, we divided the patients into 2 groups: DC group and standard care group. Between 2010 and 2014, a total number of 223 severe TBI patients, containing 112 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…31,32 The contrasting result could be due to the small number of studies in the present analysis that included older patients and the corresponding definition of t others as >70 years, resulting in exclusion of patients between 60 and 70 years of age. 33 The DESTINY II trial provides the strongest evidence so far for DC in older patients. Although case fatality was comparable with younger patients, functional outcome was worse in the older patients compared to the younger group in previous trials (19% versus 4%).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The contrasting result could be due to the small number of studies in the present analysis that included older patients and the corresponding definition of t others as >70 years, resulting in exclusion of patients between 60 and 70 years of age. 33 The DESTINY II trial provides the strongest evidence so far for DC in older patients. Although case fatality was comparable with younger patients, functional outcome was worse in the older patients compared to the younger group in previous trials (19% versus 4%).…”
Section: Discussionmentioning
confidence: 99%
“…Our RPA model provides two nodes separated by the status of the basal cistern in patients with a GCS of 6 to 8. Studies have shown that the presence or absence of basal cistern obliteration on the CT scan image is strongly associated with the prognosis of the patient 14,16,24) . Toutant et al 21) reported that a 77% mortality rate was observed when basal cistern obliteration existed.…”
Section: Discussionmentioning
confidence: 99%
“…The HS accounts for nearby 30% of all types of acute stroke and usually has poorer prognostic Ivyspring International Publisher outcomes as compared to those of IS. Additionally, acute HS (i.e., AHS) patients who required surgical intervention will frequently develop permanent disability [5][6][7][8][9][10][11]. Furthermore, there is no data as to whether the pharmacomodulation is beneficial in patients who suffer from AHS and survive with permanent disability.…”
Section: Introductionmentioning
confidence: 99%